Aplicación del proceso contable de la NIC 2 en la empresa Comercial Katita del cantón Urdaneta - Ponce Parraga, Shirley Sulexy (2020)
The application of nic 2 aims to prescribe the accounting treatment of inventories; Inventories are tangible goods, sets of merchandise or items that are intended for sale, in commercial companies it is important to keep of systematized inventory control it allows us to know exactly the entry and exit of products that the company has, in the same way Businesses whatever the type or size must perform inventory rotation so that they can analyze the situation of their inventories and make optimal decisions, the company commercial Katita does not have an inventory control system or a person trained to carry the respective control, reason why the present case study arises.